RESERVOIR CHARACTERIZATION IN âKDSâ FIELD, KUTAI BASIN USING EXTENDED ELASTIC IMPEDANCE INVERSION - Dearmando, Kevin
The hydrocarbon needs for daily life purpose is quite high, to fulfill it is necessary to develop a hydrocarbon field and characterized the reservoir. One of the hytdrocarbon field is “KDS” field that located in Kutai Basin, Central Kalimantan with the main target located in Berai formation. For characterization of reservoir it needs seismic and well data. Well data can derive a sensitive parameter that can distinguish between reservoir and non-reservoir. The sensitive parameter than used for inversion on seismic data using extended elastic impedance (EEI) method. EEI method can delineate the sensitive parameter to separate between fluid and lithology. In this research Mu-Rho is used as the sensitive parameter that can delineate lithology and Lambda-Rho parameter is used as the sensitive parameter that can delineate fluid. EEI method is done by using AVO analysis and optimum angle of the elastic parameter. Mu-Rho optimum angle is -43o and Lambda-Rho optimum angle is 15o. After EEI volume made, then the initial model is built. The model is used for the linear programing sparse spike inversion. The inversion result than sliced and flattened, from the result it was found that in this field there is a porous carbonate which is characterized by low Mu-Rho. This is related to the well area that was a height in the past and located in the rim of the carbonate platform. Also there is a fluid-filled zone on the porous carbonate that characterized by low Lambda-Rho.